Which antibiotics should I use? - Shalihin, Mohd Shaiful Ehsan (Which Antibiotics Should I Use, 2015)
“Which antibiotic should I use?” It’s a question we ask ourselves when we want to initiate antibiotic treatment for our patients. When patients approach us at the clinic or hospital with fever or other symptoms of infection, they hope that they will be treated correctly. That includes prescribing the appropriate antibiotic. Sometimes, patients request for the most elaborate broadspectrum antibiotics. But do we need to eliminate as many pathogens as possible? The answer is definitely not.